Technical reporting in digital forensics - Horsman, Graeme (Wiley, 2022)
One of the primary roles of a practitioner in the field of digital forensics (DF) is to conduct the examination of any lawfully seized digital device content and report upon any findings that may support an inquiry being conducted. While there are many intricacies to this task, in some cases, an inquiry will commence with a practitioner carrying out the necessary examination work required to report any findings at a “technical level.” Such technical reports are often used for intelligence gathering purposes in an attempt to establish the potential evidential value of a device or data set and are often a precursor to, and catalyst for, further and often more extensive forensic work being commissioned. Therefore, the ability to report at a technical level should be considered a fundamental skill required of all practitioners in this discipline and any attempts to provide guidance and support for conducting this task effectively should be encouraged. This work explores the role of technical reporting, where a series of reporting examples are presented that explore the intricacies involved with conveying digital forensic findings at a technical level. Procedural and linguistic challenges are investigated and evaluated in order to acknowledge the pitfalls that practitioners may encounter and to identify potential technical reporting best practices.
Keywords: digital evidence; digital forensics; report writing; technical reporting